Field reports form for submitting seasonal observations of Iowa birds, Matthew Kenne, fall 1997 - Kenne, Matthewet al (1997)
Fall report of birds found in northern Iowa contributed by Matthew Kenne. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed